Turkic World: Actual Problems - D. S. Zheriborov (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article reports on the international conference “Turkic World: Actual Problems,” which took place at the Ural Federal University in October 2017. In the conference took part scientists from Russia, Azerbaijan, Kazakhstan, Kyrgyzstan, Turkey, Uzbekistan.